Older, vulnerable patient view: a pilot and feasibility study of the patient measure of safety (PMOS) with patients in Australia - Jeffrey Braithwaite; Natalie Taylor; Rebecca Lawton; Robyn Clay-Williams; Emily Hogden; Zhicheng Li (BMJ Open)
Objectives The UK-developed patient measure of safety (PMOS) is a validated tool which captures patient perceptions of safety in hospitals. We aimed (1) to investigate the extent to which the PMOS is appropriate for use with stroke, acute myocardial infarction (AMI) and hip fracture patients in Australian hospitals and (2) to pilot the PMOS for use in a large-scale, national study ‘Deepening our Understanding of Quality in Australia’ (DUQuA).Participants Stroke, AMI and hip fracture patients (n=34) receiving care in 3 wards in 1 large hospital.Methods 2 phases were conducted. First, a ‘think aloud’ study was used to determine the validity of PMOS with this population in an international setting, and to make amendments based on patient feedback. The second phase tested the revised measure to establish the internal consistency reliability of the revised subscales, and piloted the recruitment and administration processes to ensure feasibility of the PMOS for use in DUQuA.Results Of the 43 questions in the PMOS, 13 (30%) were amended based on issues patients highlighted for improvement in phase 1. In phase 2, a total of 34 patients were approached and 29 included, with a mean age of 71.3 years (SD=16.39). Internal consistency reliability was established using interitem correlation and Cronbach's α for all but 1 subscale. The most and least favourably rated aspects of safety differed between the 3 wards. A study log was categorised into 10 key feasibility factors, including liaising with wards to understand operational procedures and identify patterns of patient discharge.Conclusions Capturing patient perceptions of care is crucial in improving patient safety. The revised PMOS is appropriate for use with vulnerable older adult groups. The findings from this study have informed key decisions made for the deployment of this measure as part of the DUQuA study.